Using Linux performance tools : learn how to monitor, profile, and trace Linux systems and applications - Goldshtein, Sasha (O'Reilly, 2017)
"Move from basic Linux administration to advanced in this course that details how to monitor, profile, and trace Linux systems and applications. Linux expert Sasha Goldshtein shows you how to run basic performance checklists to get a reading of high-level system performance. You'll discover ways to diagnose specific issues such as high CPU load, excessive I/O, and slow network requests; as well as gain a solid understanding of the Linux system infrastructure that makes tracing and profiling possible. The course is designed for application developers, system administrators, and SREs with some Linux system administration experience and a basic understanding of OS concepts like threads, I/O operations, and memory."--Resource description page